Strategy for Improving Human Resources Quality Through Training and Brainstorming - Muhammad Imam Mawardi; Nur Cahyadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Human resources (HR) are the most important asset in an organization. Human resources are a very important element for a company because they are the driving force of a company's internal activities. High-quality talent contributes directly to a company's productivity, innovation and competitiveness. The role of employees in a company can be measured by their performance. Employee performance is a measure of the results achieved by an employee and determines whether the employee is still suitable or the employee has a problem that affects the company's performance. Training provides opportunities for employees to develop skills and knowledge relevant to their duties and responsibilities. This not only improves individual competencies, but also builds a culture of learning within the organization. This research uses a qualitative descriptive approach. This research uses primary data and secondary data as research data to be used. The results showed that training and brainstorming are strategies that can be used to improve the quality of human resources at PT Cipta Qawafil Alshafa. Well-conducted training can improve employee performance, while brainstorming can encourage creativity and invasion in solving problems. With a more structured strategy and proper evaluation, the company can continue to grow and increase competitiveness in the market.